VD_FINDINFO HC / 2011 / 147 vom 17. Februar 2011 - VD Tribunal cantonal (2011)
SALAIRE, LOI FÉDÉRALE SUR L'ÉGALITÉ ENTRE FEMMES ET HOMMES | 343 CO, 444 CPC, 445 CPC, 451 CPC, 452 al. 2 CPC, 465 al. 1 CPC, 3 LEg, 6 LEg, 46 al. 1 LJT, 46 al. 2 LJT, 405 al. 1 CPC (CH)